KEBERLANGSUNGAN PENGHIDUPAN MASYARAKAT PERDESAAN PADA PEMBANGUNAN WADUK CIAWI DAN SUKAMAHI - Mauluddin, Agus; Safwan, Safwan (TEMALI : Jurnal Pembangunan Sosial, 2019)
In the minds of the community, every eviction creates anxiety. Because the place of residence embedded in the meaning and memory in it will be evicted. Unlike the case with the eviction of land (not settlements), which is active or not. Because the landowners in the village are mostly from outside the village (local people call the people of Jakarta). This study uses a qualitative approach that looks at the holistic picture of the object of research in explaining the social phenomena under study, namely the impact of evicting the construction of the Ciawi and Sukamahi reservoirs. The data collection technique used in this study is the RRA method, to accurately collect information in a limited time when decisions about rural development must be taken immediately. Basically, the RRA method is an intensive learning process to understand rural conditions, carried out repeatedly, and quickly. With the research approaches and methods used, this study produced several conclusions and recommendations, including, First, the Government must provide new residential land and with collective relocation. Second, the government must maintain socio-cultural, customs that are usually routinely carried out in the village, are maintained and also provide a place to build facilities for worship infrastructure, such as mosques, and table society of religion, even though the place for burial. Third, the government provides enough land (relocation sites) for the community, which can be used as a place of residence accompanied by sufficient land and in one location. Fourth, in each of its policies, the government pays attention to and is able to maintain the capital owned by the community, such as between social capital (networking). The government is not only limited to completing its duties and obligations, such as providing compensation, but its community unity (social capital) is not considered.